Um estudo sobre empresas de capital aberto brasileiras e norte-americanas do setor construção civil nos períodos ex-ant e ex-post a crise subprime - Brito, Ana Fátima de (2012)
From its beginning in 2007, the U. S. Subprime Crisis can be considered the largest one occurred in the century so far, mainly for its extension, since shortly after the release of the first facts, many countries have shown signs of having been contaminated by its effects. Moreover, other nations such as Brazil sought to say that would not be affected, given the solid basis that its economy has shown. Brazil really showed signs of improvement in the economy a few years before the crisis: Gross Domestic Product - GDP was growing, inflation was under control and the employment level improved. By contrast, the United States had problems in the stock market in 2000 and had suffered the biggest terrorist attack in its history in 2001, which led to an outbreak of wars in other countries. This situation generated a bad effect on the U.S. economy, since the level of employment did not improve and prices rose, mainly on real estate assets. Many signs of problems in the U.S. economy were released, mainly the huge appreciation in real estate prices. In early 2007, companies in the mortgage industry began to have financial problems, however it was in August, when the French bank BNP Paribas announced the suspension of investment funds with roles in applications related to the mortgage that the world turned its look at the U.S. housing market. Throughout the following months, as the situation did not improve, many companies divulged disclosed financial problems and went bankrupt, such as Lehman Brothers, a hundred years old banking institution., which announced its bankruptcy in September 2008. Such a troubled scenario on the U.S. inspired this research to evaluate the effects of the crisis on the stock price of companies in the American an Brazilian Building sector. The industry was chosen due to its importance in generating employment, recent expansion of the real estate sector in Brazil and its link to the U.S. mortgage contracts. Five U.S. construction companies and also 5 Brazilian companies with publicly exchanged stocks were chosen. We selected the event study technique to accomplish the work. We found that the two facts related to Banco BNP Paribas and the bankruptcy of Lehman Brothers generated abnormal returns in stock prices of those 10 companies in the days preceding and following the disclosure of facts,, which contradicts the postulated assumption of the efficient market theory: that given that the market rationality and prices are adjusted to the information disclosed, the expected return is normal,